Exhuming the Present to Reinter the Past (KULT_online, 2017)
In 2012, in a carpark in the city of Leicester, the skeletal remains of King Richard III of England, thought long lost, were found shortly after the identification of the site of the Grey Friars monastery where they were documented as having been buried after his defeat and death at the Battle of Bosworth in 1485. The book How to Bury a King by Pete Hobson recounts how the manner of their reburial was decided, and in doing so provides a fascinating insight into the thoughts behind an event used for local and national identity building in the 21st century.